Natural resources, export concentration and financial development - Christian Hattendorff (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
Recent studies indicate that the natural resource curse, that is, the negative link between resource abundance and growth, may operate through a country's financial system. Scholars show that resource-abundant economies suffer from lower financial development, which may indirectly affect welfare. The present study provides an explanation for this financial channel. It argues that resource-rich countries are likely to have a concentrated export structure, causing a reduction of the financial system's size due to volatility and the associated high real interest rates. The paper shows empirically that export concentration tends to weaken private credit to GDP. The analysis builds on cross-sectional and panel data from 93 countries for the period 1970-2007. The direction of causality is tested with an instrumentation strategy using geographic and geospatial variables as well as dynamic panel techniques.
Keywords: F10; F40; G10; O13; O16; 330; natural resources; export concentration; financial development; volatility; geography